Dual-species biofilms of Candida tropicalis isolated from apple juice ultrafiltration membranes, with Escherichia coli O157:H7 and Salmonella sp. - Tarifa, Maria Clara (2015)
Aims: The objective of this study was to determine the interactions between common spoilage yeast, Candida tropicalis, isolated from ultrafiltration membranes, and Escherichia coli O157:H7 and Salmonella sp. on stainless steel surfaces. / Methods and Results: Single and dual-species attachment assays were performed on stainless steel at 25°C using apple juice as culture medium. The growth of Salmonella sp. rose when it was co-cultivated with C. tropicalis in dual biofilms at 16 and 24 h; the same effect was observed for E. coli O157:H7 at 24 h. The colonization of C. tropicalis on stainless steel surfaces was reduced when it was co-cultivated with both pathogenic bacteria, reducing C. tropicalis population by at least 1·0 log unit. Visualization by SEM demonstrated that E. coli O157:H7 and Salmonella sp. adhere closely to hyphal elements using anchorage structures to attach to the surface and other cells. / Conclusions: These results suggest a route for potential increased survival of pathogens in juice processing environments. These support the notion that the species involved interact in mixed yeast–bacteria communities favouring the development of bacteria over yeast. / Significance and Impact of the Study: This study support the plausibility that pathogen interactions with strong biofilm forming members of spoilage microbiota, such as C. tropicalis, might play an important role for the survival and dissemination of E. coli O157:H7 and Salmonella sp. in food-processing environments.